Intelligent spin states constructed from SU q(2) coherent states - Reboiro, Marta (2015)
It is shown that q-deformed Coherent Spin States (CSS), belonging to the SUq(2) representation, behave as Intelligent Spin States (ISS). The proof is based on the calculation of spin-squeezing observables, for both CSS and ISS.